La acumulación de las penas y su impacto en el índice de criminalidad en el derecho comparado americano. - Baldeón Echeverría, Santiago Xavier (2023)
The main purpose of this research study was to focus on punishment which refers to a legal sanction that restricts a person's rights as a consequence of committing an offence previously defined by law. For a penalty to be applied, an individual must be found guiltyof committing an offense, which implies that an unlawful act has been committed against another person. The purpose of sentencing is both general prevention of crime, by deterring society, and special prevention, by seeking the rehabilitation and reintegration of the offender into society. A more balanced approach to criminal justice is now being promoted, focusing on rehabilitation and reintegration of offenders as effective strategiesto reduce crime. The accumulation of sentences in America refers to the legal process inwhich a person convicted of multiple offenses receives additional sentences for each offense, resulting in a longer total time of imprisonment. The application of this practicevaries according to the laws and legal context of each country, with differences in its strictness. The purpose is to reflect the seriousness of the offenses and to ensure that the consequences of the offender's actions are enforced, although concerns are raised about the fairness of imposing excessively long sentences. Some countries are pushing for reforms with a focus on rehabilitation and social reintegration of offenders. Countries, such as Canada, Mexico, Chile, and Argentina, follow their approaches to the accumulation of sentences, guided by their respective legal frameworks and penal policieswith variations in the application and time limits for serving sentences. In Ecuador, although the accumulation of sentences is allowed, the rehabilitative orientation clashes with the maximum accumulation of 40 years. The lack of resources poses significant challenges for the Ecuadorian prison system, affecting the rehabilitation and re- socialization of offenders.